ASSESSMENT OF MICRO ESTHETICS IN PATIENTS REPORTING FOR ORTHODONTIC TREATMENT (Journal of Pharmaceutical Negative Results, 2022)
Background: Patients today seeking esthetic treatment are looking for enhancement of their appearance for improved quality of life. We advocate the use of the term “appearance” in conjunction with the term “esthetics'' because it involves a broader assessment of the patient other than the smile. So, in orthodontic diagnosis and treatment planning we have created an approach in evaluation divided into three divisions:1 Macro Esthetics—this includes the profile, vertical facial dimensions—in other words—the face. (2)Mini Esthetics—the smile attributes—buccal corridors, smile arc, incisor display, etc. (3) Micro esthetics—the teeth and their many attributes such as contacts and connectors, embrasures, gingival shape and contour.Aim: The aim of this is to the micro esthetics in patients reporting for orthodontic treatment in Saveetha Dental College.Material and Methods: This is a retrospective clinical study carried out at Saveetha Dental College, Chennai. This study involves the assessment of micro esthetics in patients reporting for orthodontics treatment. The data were taken over a period of 2 years from June 2019 to February 2021. The sample/data were retrieved based on micro esthetics , crown length and width ratio, gingival embrasures, midline, tooth shape.Results: According to the study 66% of the individuals had different crown length and crown width ratio and 34% of individuals had the same crown length and crown width ratio. Most of the patients had midline deviations.Conclusion: Within the limits of the study most of the patients have micro esthetic assessment after orthodontic treatment.